2021
DOI: 10.3390/ijms22020918
|View full text |Cite
|
Sign up to set email alerts
|

Functional Inactivation of Drosophila GCK Orthologs Causes Genomic Instability and Oxidative Stress in a Fly Model of MODY-2

Abstract: Maturity-onset diabetes of the young (MODY) type 2 is caused by heterozygous inactivating mutations in the gene encoding glucokinase (GCK), a pivotal enzyme for glucose homeostasis. In the pancreas GCK regulates insulin secretion, while in the liver it promotes glucose utilization and storage. We showed that silencing the DrosophilaGCK orthologs Hex-A and Hex-C results in a MODY-2-like hyperglycemia. Targeted knock-down revealed that Hex-A is expressed in insulin producing cells (IPCs) whereas Hex-C is specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Reactive oxygen species (ROS) measurement was performed in larval hemolymph from larvae reared in standard, PLP‐ or AA‐supplemented medium, using the nitro blue tetrazolium (NBT) as previously described (Mascolo et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) measurement was performed in larval hemolymph from larvae reared in standard, PLP‐ or AA‐supplemented medium, using the nitro blue tetrazolium (NBT) as previously described (Mascolo et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A model of MODY2 was generated by Mascolo and co-workers [ 144 ]. Differently from mammals which possess only one GCK gene and different tissue-specific isoforms, Drosophila has two main GCK orthologs: Hex-C expressed in the fat body and Hex-A expressed in IPCs, which perform the functions of hepatic and pancreatic mammalian GCK, respectively [ 144 ]. Moreover, Hex-A is required for insulin secretion and to trigger the expression of Hex-C in the fat body [ 144 ].…”
Section: Drosophila As a Diabetes Modelmentioning
confidence: 99%
“…Differently from mammals which possess only one GCK gene and different tissue-specific isoforms, Drosophila has two main GCK orthologs: Hex-C expressed in the fat body and Hex-A expressed in IPCs, which perform the functions of hepatic and pancreatic mammalian GCK, respectively [ 144 ]. Moreover, Hex-A is required for insulin secretion and to trigger the expression of Hex-C in the fat body [ 144 ]. RNAi-induced silencing of Hex-A or Hex-C genes resulted in diabetic phenotypes similar to those observed in MODY2 patients.…”
Section: Drosophila As a Diabetes Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third study, Mascolo et al generated a fly model of MODY-2, a rare human disorder caused by pathogenic variants in glucokinase (GCK). By knocking down the fly homologs of GCK, the authors found that this manipulation leads to genomic instability, likely caused by reactive oxygen species production triggered by advanced glycation end-products [5]. The authors further showed that treating MODY-2 model flies with an antioxidant vitamin B6 can suppress this phenotype, suggesting potential therapeutic avenues for this disorder.…”
mentioning
confidence: 98%